Early evolution and three-dimensional structure of embedded star clusters. Issue 1 (23rd February 2023) - Cournoyer-Cloutier, Claude; Sills, Alison; Harris, William E; Appel, Sabrina M; Lewis, Sean C; Polak, Brooke; Tran, Aaron; Wilhelm, Martijn J C; Mac Low, Mordecai-Mark; McMillan, Stephen L W; Portegies Zwart, Simon
ABSTRACT: We perform simulations of star cluster formation to investigate the morphological evolution of embedded star clusters in the earliest stages of their evolution. We conduct our simulations with Torch, which uses the Amuse framework to couple state-of-the-art stellar dynamics to star formation, radiation, stellar winds, and hydrodynamics in Flash . We simulate a suite of 10 4 M⊙ clouds at 0.0683 pc resolution for ∼2 Myr after the onset of star formation, with virial parameters α = 0.8, 2.0, 4.0 and different random samplings of the stellar initial mass function and prescriptions for primordial binaries. Our simulations result in a population of embedded clusters with realistic morphologies (sizes, densities, and ellipticities) that reproduce the known trend of clouds with higher initial α having lower star formation efficiencies. Our key results are as follows: (1) Cluster mass growth is not monotonic, and clusters can lose up to half of their mass while they are embedded. (2) Cluster morphology is not correlated with cluster mass and changes over ∼0.01 Myr time-scales. (3) The morphology of an embedded cluster is not indicative of its long-term evolution but only of its recent history: radius and ellipticity increase sharply when a cluster accretes stars. (4) The dynamical evolution of very young embedded clusters with masses ≲1000 M⊙ is dominated by the overall gravitational potential of the star-forming region rather than by internal dynamical processes such as two- or few-body relaxation.